Western Diet Decreases Hepatic Drug Metabolism in Male LDLr−/−ApoB100/100 Mice - Markus Koponen; Jaana Rysä; Anna-Kaisa Ruotsalainen; Olli Kärkkäinen; Risto O. Juvonen (Journal of Nutrition and Metabolism)
Consumption of a Western diet is an important risk factor for several chronic diseases including nonalcoholic fatty liver disease (NAFLD), but its effect on the xenobiotic metabolizing enzyme activities in the liver has been studied incompletely. In this study, male LDLr−/−ApoB100/100 mice were fed with Western diet (WD) or a standard diet for five months to reveal the effects on drug metabolism such as cytochrome P450 (CYP) oxidation and conjugation activities in the liver. Hepatic steatosis, lobular inflammation, and early fibrosis were observed in WD fed mice, but not in chow diet control mice. When compared to the controls, the WD-fed mice had significantly decreased protein-normalized CYP probe activities of 7-ethoxyresorufinO-deethylation (52%), coumarin 7-hydroxylation (26%), 7-hydroxylation of 3-(3-fluoro-4-hydroxyphenyl)-6-methoxycoumarin (70%), 7-hydroxylation of 3-(4-trifluoromethoxyphenyl)-6-methoxycoumarin (78%), 7-hydroxylation of 3-(3-methoxyphenyl)coumarin (81%), and pentoxyresorufin O-depentylation (66%). Increased activity was seen significantly in sulfonation of 3-(4-methylphenyl)-7-hydroxycoumarin (289%) and cytosol catechol O-methyltranferase (COMT, 148%) in the WD group when compared to the controls. In conclusion, the WD-induced steatosis in male LDLr−/−ApoB100/100 mice was associated with decreased CYP oxidation reactions but had no clear effects on conjugation reactions of glucuronidation, sulfonation, and cytosolic catechol O-methylation. Consequently, the WD may decrease the metabolic elimination of drugs compared to healthier low-fat diets.